2020
DOI: 10.3390/w12041194
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Sources of Major Ions in Hot Springs in the Triassic Carbonates of Chongqing, China

Abstract: Thermal groundwater in the Lower and Middle Triassic carbonates in Chongqing, China, is mainly concentrated in anticlines. Hot springs (32.9 to 57 °C) with SO4-Ca type waters and Total Dissolved Solids (TDS) of 1620 to 2929 mg/L emerge in the middle and the plunging ends of the structures. Multivariate methods are used to analyze the hydrochemical characteristics of the waters, and identify the sources of the main dissolved components, providing an insight into the evolution of the environment in which they fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…R-type FA is a type of data simplification technique. By studying the original variables with good interrelationship, the basic data structure is represented by simplified common factors, which are irrelevant or orthogonal to each other [23,33]. FA mainly involves the following steps.…”
Section: Factor Analysis (Fa)mentioning
confidence: 99%
See 1 more Smart Citation
“…R-type FA is a type of data simplification technique. By studying the original variables with good interrelationship, the basic data structure is represented by simplified common factors, which are irrelevant or orthogonal to each other [23,33]. FA mainly involves the following steps.…”
Section: Factor Analysis (Fa)mentioning
confidence: 99%
“…Statistical analysis based on multivariate statistical theory, such as correlation matrix (CM), cluster analysis (CA), principal component analysis (PCA), factor analysis (FA), and discriminant analysis (DA), can be used to study the relationship and influence between variables. By extracting the mathematical characteristics of the data, water quality factors can be described macroscopically, and the spatiotemporal distribution of hydrochemistry can then be analyzed [23]. This improves the understanding of the geological origin and environmental origin of soluble ions and metals in water [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2020) pointed out that due to the high pCO 2 values (10-3.5 atm) in geothermal spring water and the escape of CO 2 from water after the spring water emerged from the surface, CaCO 3 was deposited to form travertine [23]. Ta et al (2020) discussed the evolution and source of major ions in triassic carbonate hot springs in Chongqing. These related studies revealed the source and migration of CO 2 gas in hot springs from different perspectives [24].…”
Section: Introductionmentioning
confidence: 99%
“…Ta et al (2020) discussed the evolution and source of major ions in triassic carbonate hot springs in Chongqing. These related studies revealed the source and migration of CO 2 gas in hot springs from different perspectives [24].…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal springs and karst landform have been characterized as the specific geological conditions in Chongqing. In recent decades, numerous studies have been carried out for the genesis of geothermal springs which exist as deep groundwater at the local scale [23][24][25][26][27][28]. In contrast, the hydrogeochemical process of shallow groundwater, especially at the regional scale, remains controversial and has yet to be further investigated.…”
Section: Introductionmentioning
confidence: 99%